Investigation of hydrodynamic processes of a ladle bath when blown through bottom blower devices - Ruban , V.O.; Stoyanov , O.M.; Musiko , V.I.; Shashkin , T.A.; Marko , A.F. (Theory and Practice of Metallurgy, 2024)
The object of study is the hydrodynamic processes of the ladle bath during blowing through bottom blowers. The purpose of the study is to establish the basic principles of the bubbling zone formation and its effect on the slag layer, as well as to evaluate the efficiency of non-metallic inclusions removal during out-of-furnace steel treatment at the ladle-furnace unit. The state of the art of out-of-furnace steel treatment at the ladle-furnace unit has been studied, which has shown that the efficiency of this unit is significantly influenced by blowing, including the location of bottom blower blocks and the intensity of mass transfer. Based on the analysis of the literature, an experimental methodology was developed and a laboratory setup for physical modeling on a cold model was created. Mathematical models have been created on the basis of which the influence of technological factors such as blowing modes, location of blowing devices, slag height on neutral gas consumption and, in turn, on changes in material and energy consumption of steel during out-of-furnace treatment can be described. It is determined that an increase in the blowing intensity leads to an increase in the efficiency of non-metallic inclusions removal due to a larger bubbling zone, in particular, the percentage of inclusions removed increases from 8% at 100 l/min to 22% at 800 l/min of gas flow. In addition, the influence of various parameters, such as the location of the blowdown blocks, on the interaction of the gas flow with metal and slag, as well as their impact on the formation of the blowdown spot and the temperature of the metal bath is described. The results of physical modeling and mathematical models make it possible to optimize the processes of out-of-furnace steel treatment, which contributes to improving the quality of finished products.